2003
DOI: 10.1507/endocrj.50.759
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia and Obesity in Adult Patients with Hypopituitarism: A Report of a Nation-wide Survey in Japan

Abstract: Abstract. Dyslipidemia and obesity are common in adult patients with hypopituitarism. Possible contributions of age, sex and hormone deficiencies to hypercholesterolemia and obesity in adult hypopituitary patients were analyzed in 1, 272 Japanese cases based on a database of a national survey on adult hypopituitarism. In patients on routine hormone replacement therapy, 30.5% of male and 40.7% of female subjects were considered hypercholesterolemic. In univariate analysis, hypercholesterolemia was more prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
4
8
1
Order By: Relevance
“…The higher prevalence of obesity was in good agreement with a previous report [11]. It is likely that the result is secondary to an excess food intake from hypothalamic dysfunction supposed to be more frequent in such patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The higher prevalence of obesity was in good agreement with a previous report [11]. It is likely that the result is secondary to an excess food intake from hypothalamic dysfunction supposed to be more frequent in such patients.…”
Section: Discussionsupporting
confidence: 92%
“…In our previous study of similar subjects using univariate analysis, serum total cholesterol levels only in men were significantly higher in GHD than in non-GHD, but the prevalence of hypercholesterolemia was not significantly different between GHD and non-GHD both in men and women [4]. Therefore, this finding was not only consistent with our previous report that cardiovascular disease in adult GHD was less prevalent than expected in Japan [4] but also with others report that there was no association between GHD and either hypercholesterolemia [11,16,17] or obesity [11]. On the other hand, some investigators reported the increased total cholesterol levels in GHD [18][19][20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Epidemiological studies have shown that this abdominal obesity is a risk factor for development of metabolic abnormalities leading to cardiovascular complications [4,5]. In studies in Japanese adult patients with GHD it has been shown that there is an increased risk of cardio-and cerebro-vascular morbidity and mortality compared to the normal population [6][7][8], similar to that previously shown in Caucasian patients [5,[9][10][11].…”
supporting
confidence: 65%
“…About 30% of the subjects in the present study had a total cholesterol value higher than the Framingham threshold for cardiovascular risk; this would indicate an approximately fourfold increase in risk compared with the general population and confirms our interpretation of the BMI and FM data. High total cholesterol concentrations were reported for hypopituitary patients in a national survey in Japan (18). However, it was reported that the hypercholesterolaemia was associated with untreated gonadotrophin and thyrotrophin deficiencies and not with GHD.…”
Section: Ao Patients Co Patientsmentioning
confidence: 96%